The Effect of Service Quality, Customer Experience and Price Discount on Customer Satisfaction at Golden Lamian Plaza Medan Fair - Mutia, Mutiara Putri Br. Ginting; Pohan, Yuli Arnida (CV. Civiliza Publishing, 2025)
This study aims to find out and analyze the partial and simultaneous influence of Service Quality, Customer Experience and Price Discount on Consumer Satisfaction at Golden Lamian Plaza Medan Fair. The type of research used in this study is causal associative research with quantitative methods. The population in this study are consumers who are visiting or have visited the Golden Lamian Plaza Medan Fair. The sampling technique in this study is to use the non-probability sampling method with accidental sampling technique. To determine the sample size, the researcher used the lameshow formula. The number of research samples taken in this study was rounded from 98 to 120 respondents to avoid biased data. The results of the study in the partial test showed that Service Quality had a positive and significant effect on Consumer Satisfaction, Customer Experience had a positive and significant effect on Consumer Satisfaction and Price Discount did not have a positive and significant effect on Consumer Satisfaction. Meanwhile, the results of the study in the simultaneous test showed that Service Quality, Customer Experience and Price Discount together had a positive and significant influence on Consumer Satisfaction at Golden Lamian Plaza Medan Fair. A adjusted value R square 0.232 can be called the determination coefficient, this means that 0.232 (23.2%) Consumer Satisfaction can be obtained and explained by Service Quality, Customer Experience and Price Discount while the remaining 76.8% is explained by variables outside the model that were not studied.